Concept Understanding of Science in The Project Based Learning Model Using Recycling Activities - Apriana, Wendi Nilpa; Ridlo, Saiful; Latiana, Lita (Journal of Primary Education, 2019)
This study was aimed to determine the level of classical completeness of student learning outcomes in the project based learning model by using recycling activities to describe the difference in concept understanding of science the experiment and control classes. The population in this study was the fifth grade students of SDN Setramanah, Subang District, Subang Regency 2018/2019 Academic Year. The type of research used in this study was a quasi-experimental design with nonequivalent control group design. The data analysis was done using the proportion test and the independent samples t-test. The results of this study showed that the completeness of concept understanding of science was more than 75%; and the ability of concept understanding in the project based learning model using recycling activities is was better than that of the project based learning model without recycling activities.